Association between intergenerational solidarity involving elders and mental health of Indigenous people living off reserve - Chantal Viscogliosi; Hugo Asselin; Lise Trottier; Monia D'Amours; Mélanie Levasseur (BMC, 2022)
Abstract Background Indigenous elders play an important role in transmitting knowledge, values and practices, hence fostering identity-building through intergenerational solidarity. We aimed to verify the association between intergenerational solidarity involving Indigenous elders and mental health of Indigenous people living off reserve. Methods We carried secondary analyses of data for a subsample from the cross-sectional 2012 Aboriginal Peoples Survey (total sample: n = 28,410 Indigenous persons aged ≥6 years old living off reserve; subsample: n = 13,020 aged 18-44 years old). Controlling for age as well as material and social deprivation, we used logistic regressions to verify the association between intergenerational solidarity (proxied as time spent with an elder and potential of turning to an elder or grandparent for support in times of need) and mental health (perceived mental health, mood disorders, anxiety, suicidal thoughts and attempts). Results About 39 and 9% of the respondents respectively reported having spent time with an elder and would have turned to an elder or grandparent for support in times of need. Women who would not turn to an elder or grandparent for support in times of need were more likely to report fair or poor perceived mental health (OR = 1.69, p = 0.03). Men not spending time with an elder were more likely to experience mood disorders (OR = 1.66, p = 0.004). Women who would not turn to an elder or grandparent for support in times of need were more likely to experience anxiety disorders (OR = 1.57, p = 0.04). Women not spending time with an elder or who would not turn to an elder or grandparent for support in times of need were respectively more likely to have suicidal thoughts (OR = 1.62, p = 0.04) or to have attempted suicide (OR = 3.38, p = 0.04). Conclusion Intergenerational solidarity is associated with better mental health outcomes of Indigenous people living off reserve. These results could guide policies and practices that aim to enhance mental health and wellness in Indigenous populations.